PENAMBAHAN 6-BENZIL AMINO PURINE (BAP) DAN ASAM NAFTALENASETAT (NAA) BERHASILMENGINDUKSI PEMBENTUKANDAN PEMANJANGAN TUNAS MERBAU (INTSIA BIJUGA (COLEBR.) O. KUNTZE)SECARA IN VITRO - Kiki Ernawati; Arief Husin; Sisunandar Sisunandar (Universitas Sebelas Maret, 2014)
Abstract - Merbau(Intsia bijuga(Colebr.) O.Kuntze) is one of the most valuable wooden tree in Indonesia because of the high price and the international highly demanding on it continue to rise up every year.On the other hand,due to an excessive exploitation and unsuccesful reforestation programs resulted on a status of a vulnerable species of the tree. The seedling production of the species using traditional technique is still limited to overcome the problems because of the low number of the seed production every year. One of the most posible approch for mass rapid plantlets production of merbau is using shoot tip culture. However, the protocol of merbau shoot tip culture is still not well developed since the success rate of shoot induction remains low (less than 15 %), no multiplication, root induction and acclimatisation step are aplicable. Our results indicate that DKW medium(Driver and Kuniyuki, 1984) suplemented with 10-6 MNAA and 10-6 MBA Pinduce shoots formation fromaxillary budex plant with a success rate up to 80%. The number of shoots produced from each explant was two shoots with six internodes and quite tall (4,5 cm). The multiplication can be done by the sub-culture the axilary buds into fresh medium every four weeks. The next step will be induction and acclimatisation of the plant podused by shoot tip culture. Keywords:merbau, shoots-tip culture, multiplication